Hubungan Persepsi Siswa tentang Kompetensi Pedagogik Guru PKn dengan Prestasi Belajar di Kelas X SMK Muhammadiyah 1 Banjarmasin - Yulia Khairunnisa (Jurnal Pendidikan Kewarganegaraan, 2015)
Pedagogical competence is a competence a teacher has in managing students’ learning process. Besides, pedagogical competence is also indicated in giving help, guiding, and leading the students. A good pedagogical competence will result in students’ good learning achievement. Furthermore, this research aims to find out how strong the correlation between the students’ perception about pedagogical competence of civic education teachers and the students’ learning achievement. Additionally, it aims to find out the significant correlation between the students’ perception about pedagogical competence of civic education teachers and the students’ learning achievement at the tenth-grade students of SMK Muhammadiyah 1 Banjarmasin.      This research used quantitative approach with the sampling technique using table of Krejcie and Morgan. The sample was obtained randomly by lottery. In collecting the data, techniques used were observation, interview, questionnaire, and documentation. The research findings were analyzed by using descriptive analysis and testing of Product Moment correlation.  The result of this research shows that there is significant correlation between pedagogical competence of teachers and the students’ learning achievement. It is seen from the testing result of Product Moment correlation as much as 0,596, which was adjusted to table of r value interpretation. Thus, 0,596 value was categorized into coefficient interval between 0,40 to 0,599. This interval is interpreted as medium category.  Based on the result of this research, it is suggested that the school should increase the teachers’ pedagogical competence and it needs cooperation between the school and the government in order to select teachers whose high quality, are able to educate, teach, guide, lead, train, assess and evaluate the students. Therefore, this effort can increase the education quality in Indonesia.  Keywords: pedagogical competence, students’ learning achievement